Upaya Peningkatan Kebutuhan Istirahat Tidur Pada Ibu Hamil Trimester II - Meilina Palupi, Widya; , Faizah Betty R., A., S.Kep ., M.Kes (2017)
Background: Pregnancy is the process of fetal development in the woman's womb, which generally lasts about 280 days (40 weeks or 9 months 7 days). Individuals were categorized to sleep, if the individual is on the state: a minimum of physical activity and varies awareness level. Rest is a relaxed state without the emotional stress and not just in a state of activity. The second trimester period, the fetus grows from the age of 14 weeks to 24 or 25 weeks. The purpose of this research is to fulfill the needs of bed rest for pregnant women on the second trimester. The author conducted the study in February. The method used in this research is observation, interview and documentation. The results of research by the author obtained bed rest problems was caused by psychological factors (noise). Intervention conducted by the author includes: observing the comfortable environment, observing the number of hours of sleep in the normal range. After nursing intervention for 3 days rest and sleep needs can be resolved in part, so that the intervention is continued.